CUIDADOS DE ENFERMAGEM A UM CASO DE GRAVIDEZ NA ADOLESCÊNCIA: UM ESTUDO DE CASO - Crisbênia Araújo, Luiza; Monteiro da Silva, Maria Adelane; Feitosa da Silva, Antonia Michele; Sales Bezerra, Geane; Barbosa Palácio, Gerciara; Albuquerque Araújo, Luisa Stephanie; Larissa Dias Aragão, Maria (SANARE - Revista de Políticas Públicas, 2015)
-